PERLINDUNGAN HUKUM KONSUMEN TERHADAP PEREDARAN PRODUK VAKSIN PALSU - Tri Astuti; Efridani Lubis; Mohammad Zakky As (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2019)
In the Law 1945 the Unitary State of the Republic of Indonesia article 1 paragraph (3) affirmed that the State of Indonesia is a state of law. In addition, in the General Explanation of the 1945 Constitution on The System of State Government, it is explained that: Indonesia is a country based on law (Rechstaat) is not based on mere power (Machstaat). Laws are formulated to regulate and protect the interests of the community and to protect human rights. The need for law to provide Indonesian Consumer Protection is inevitable, in line with one of our national development goals, namely protecting the Indonesian nation and all Indonesian blood (the opening of the 1945 Constitution paragraph IV). In this study, the author focused on the formulation of the problem